Analysis of Lack of Work Planning: A Case Study of High Work Accidents at PT Indonesia Morowali Industrial Park - Harmen, Hilma; Anak Ampun, Grace Analita Febrina; Zahra, Saffanah Alya; Pandiangan, Raja Satrio; Situmorang, Listem Wisiska; Marpaung, Irvan Aldi Josua; Siagian, Nielsen Samuel Panahatan (Jurnal Studi Manajemen dan Bisnis, 2025)
This study aims to identify various errors that contribute to the failure of human resource management in making a safety assurance plan for workers in a company, which has an impact on providing a dangerous working environment for employees. In addition, this research also focuses on presenting strategies in the form of solutions that can be applied to overcome this problem in the context of human resource management.The method used in this study is a qualitative method, which presents descriptive theories that have a relationship with the problem, in its presentation is also supported by accurate, up-to-date data, and various literature reviews. The population that is the object of the study is employees who experience the harmful impact of the work environment in the company due to mismanagement in managing the company, which ultimately causes losses and triggers the absence of safety for workers at work. The results of this study will be in the form of an analysis of company management failures and effective strategies to be applied in company management planning to reduce the risk of a dangerous environment for workers or employees in a company.